HUBUNGAN ANTARA PENGETAHUAN KESEHATAN REPRODUKSI DENGAN PERILAKU SEKSUAL REMAJA SMA NEGERI 1 IMOGIRI - Mita Ardiyanti; Titik Muti'ah (JURNAL SPIRITS, 2013)
ABSTRACTThis study is purposed to determine the relationship between knwoledge of  reproductive health and adolescent sexual behavior in SMA N 1 Imogiri. The samples used in this study is 100 students of class X SMA Imogiri, with purposive sampling technique. The analysis of the data used in this study is the Pearson product moment correlation.The result of this study showed  the coefficient of  r=-0,939 with p=0,000, there is a negative relationship between  knowledge of reproductive health  with adolescent sexual behavior in SMA N 1 Imogiri and hypothesis was accepted. If the reproductive health knowledge goes high, making the adolescent sexual behavior  low, apply instead.Keywords: knowledge of reproductive health, adolescent bexual behavior